Proyecto de inversión para la implementación de un negocio de exportación de artesanías de tipo textil. - López, M. (2010)
Our project seeks to tap the business opportunity, one prepared the study and business plan, and have made adequate financial analysis is put into consideration: Preliminary studies determined that the current market situation is ideal for creation of a company whose business is to sell Ecuadorian handicrafts abroad, which ensures a high return. Demand in this market so special that it has experienced continuous growth over the past years, thus positioning the main strategy will be: excellent quality products at competitive prices, this proposal demonstrates its operation is a business viable and attractive with a successful utility, a marketer and efficient administrative management. After the project research, raises the following: must be registered with the specialized technical assistance in the area for a suitable business performance while taking into account the sustainable management of resources. It should assess the possibility of extending the project over the life of the product, diversifying export products, taking into account market behavior and the variables that affect it directly and preferences, prices, costs, demand and supply. Conduct market research to adequately meet customer requirements. Efficiently organize promotional activities, establishing checks and periodic adjustments in the marketing plan of the company.